The Effect of Capital Structure and Internal Audit Function Effectiveness on Company Financial Performance (Study on Banking Sector Companies Listed on the Indonesia Stock Exchange for the 2022-2024 Period) - Henni Rahayu; Ali Rahman Reza Zaputra; Marlina Marlina (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study seeks to thoroughly investigate the influence of capital structure and the effectiveness of internal audit functions on the financial performance of banking sector companies listed on the Indonesia Stock Exchange during the period from 2022 to 2024. In this research, capital structure is quantified using the Debt-to-Equity Ratio (DER), while the effectiveness of internal audits is evaluated through disclosures outlined in specific sections of POJK No. 1/POJK.03/2019. Financial performance, serving as the key outcome variable, is measured by Return on Assets (ROA). The methodology adopts a quantitative research design, incorporating purposive sampling from 46 companies across a three-year span, resulting in a total of 138 observations. Multiple linear regression analysis is applied to examine the relationships. The findings demonstrate that capital structure exerts a significant negative impact on both the effectiveness of internal auditing and overall financial performance.